Implementation of Good Corporate Governance and Capital Structure on Financial Performance - Rahma Dila Mawarni; Erma Setiawati (Transpublika Publisher, 2026)
The financial results of businesses involved in property and real estate are still encountering numerous obstacles due to the strong need for funds, risks linked to long-term projects, and fluctuations in the market. This scenario calls for clear corporate management through the adoption of effective governance practices and the establishment of the most suitable capital structure. Targeting property and real estate companies on the IDX, this research analyzes the effects of efficient corporate management (managerial ownership, institutional ownership, independent board, audit committee) and capital structure (DER) on financial outcomes from 2019 to 2023. A purposively selected sample, chosen against defined criteria, provides the data for this analysis. This research employs secondary data with a quantitative approach, sourced from the annual reports of each firm. Analyzed with multiple linear regression in SPSS 27, the data show that audit committee effectiveness and capital structure have no bearing on financial performance. Significant effects, however, are found for managerial ownership, institutional ownership, and an independent board of commissioners. This study stresses the importance of oversight in enhancing performance and offers insights for management and supervisors to reinforce governance practices within entities.